(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
This article examines the experience of the Second World War and discusses the great contribution of our compatriots, who protected their chests for the Fatherland, to the victory of the Soviet Union in the Second World War, as well as the worthy contribution of young men and women who worked tirelessly day and night and delivered goods to the front.